The Best of Both Worlds: A Pragmatic Approach to the Construction of Labour Rights as Human Rights - Walchuk, Bradley (Just Labour, 2009)
Our rights are increasingly being constructed as human rights. While this construction is gaining popularity, there is still considerable opposition to it. Recently, the debate has made its way to the pages of Just Labour. Building upon a pragmatic approach utilized by feminist legal scholars, the present article seeks to continue this important dialogue and offers an alternative that combines elements of both rights-based pluralism and critical legal scholarship. It contends that the labour movement ought to employ a multi-faceted strategy to protect and promote the rights of working people. Such a strategy recognizes the limitations of rights-discourse, but also recognize s its potential benefits. The paper argues that the labour movement cannot rely solely on rights-discourse to protect its interests but that it should also not be dismissed out of hand. Thus, the construction of labour rights as human rights can be only part of the labour movement’s broader fight back strategy.